2012
DOI: 10.1002/jbio.201200180
|View full text |Cite
|
Sign up to set email alerts
|

Long‐distance laser propulsion and deformation‐ monitoring of cells in optofluidic photonic crystal fiber

Abstract: We introduce a unique method for laser‐propelling individual cells over distances of 10s of cm through stationary liquid in a microfluidic channel. This is achieved by using liquid‐filled hollow‐core photonic crystal fiber (HC‐PCF). HC‐PCF provides low‐loss light guidance in a well‐defined single mode, resulting in highly uniform optical trapping and propulsive forces in the core which at the same time acts as a microfluidic channel. Cells are trapped laterally at the center of the core, typically several micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…There is also potential for detection of intracellular 1 O2 within the HC-PCF; the feasibility of introducing and trapping cells in the hollow core of HC-PCF has been demonstrated in one of our previous studies. [38] The present study has revealed that there are aspects of the HC-PCF technology that can be improved to achieve optimum performance in the present application. The simultaneous, efficient guidance of excitation light and luminescence is challenging, because of their disparate wavelengths.…”
Section: Discussionmentioning
confidence: 80%
“…There is also potential for detection of intracellular 1 O2 within the HC-PCF; the feasibility of introducing and trapping cells in the hollow core of HC-PCF has been demonstrated in one of our previous studies. [38] The present study has revealed that there are aspects of the HC-PCF technology that can be improved to achieve optimum performance in the present application. The simultaneous, efficient guidance of excitation light and luminescence is challenging, because of their disparate wavelengths.…”
Section: Discussionmentioning
confidence: 80%
“…Another potential application of AC-induced pressure is the optical guidance and propulsion of nanobullets inserted in hollow-core photonics crystal fibers (HC-PCF) 37 to smart drug delivery [see Fig. 4 , panel (b)].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently used our technique to laser-propel individual red blood cells over distances of 10s of cm through stationary liquid in a microfluidic channel [10] (see Fig. 2).…”
Section: Long-distance Laser Propulsion and Deformation Monitoring Ofmentioning
confidence: 99%